Biochemical, nutritional, and toxicological properties of the edible species Phlebopus beniensis with ethnomycological notes from Paraguay - Campi, Michelle (2023)
In recent decades, mushrooms have been recognized as an important resource and efforts to characterize their potential to aid nutrition and human health have increased. Phlebopus beniensis specimen from a semi-urban community in Paraguay were analyzed for its biochemical properties, nutritional value, and toxicity. The species was identified by morpho-anatomical and molecular tools. Analyses for antioxidants by Ultraviolet-visible (UV-VIS) and nutritional content revealed that P. beniensis is a favorable source of antioxidants, proteins, carbohydrates, dietary fiber, and fats. Spectrometry through Gas Chromatography-Mass Spectrometry (GC-MS) further showcased other mycochemicals such as the specific phenolic, antioxidant, and fatty acid compounds that serve important biological roles in human diets. Applying an ethnomycological framework across local Paraguayan populations, we also report accounts of histories, knowledge, and usage of P. beniensis in South America among settlers and Paraguayan people.